Analysis of Investment Effectiveness on the Painting Market – Scientific Literature Review - Lucińska, Anna (Journal of Finance and Financial Law, 2025)
In response to the growing interest in the effectiveness of investing in alternative assets, the academic community offers numerous publications on investing in works of art. The purpose of this article is to conduct a critical and comparative analysis of the most significant scientific publications on investment effectiveness in the auction market for paintings and to answer the question of the risk and effectiveness of these investments compared to traditional assets, such as stocks, bonds, real estate, commodities, and others. To achieve this stated objective, a literature review was conducted, covering 35 works that form the canon of global literature in the field of art market research. The primary criterion for selecting the publications was their citation frequency in the subject literature, considered in order of their publication. A supplementary criterion was the market being the subject of the study. Consequently, the selected publications include not only major world paintings in large, mature markets but also previously unexamined paintings and emerging art markets. No circumstances were found that would definitively allow for the formulation of a thesis presenting art as an attractive investment, particularly over a long-term horizon. The results differ depending on the period under study and the characteristics of the paintings in the research sample. Generally, rates of return are low and subject to high risk. Within a specific time and in a specific market, paintings with certain characteristics can yield higher rates of return and exhibit greater effectiveness than other assets. In mature art markets, this effectiveness was found to be lower than in financial markets but higher than in non-financial asset markets. In contrast, in emerging art markets, investment effectiveness was generally higher than that of both global financial and non-financial markets.